The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1017/s0033291708003590
|View full text |Cite
|
Sign up to set email alerts
|

Psychological treatment of social anxiety disorder: a meta-analysis

Abstract: Background. Older meta-analyses of the effects of psychological treatments of social anxiety disorder have found that these treatments have moderate to large effects. However, these earlier meta-analyses also included nonrandomized studies, and there are many featured studies in this area which were published after the recent metaanalysis.Method. We conducted a systematic literature search and identified 29 randomized studies examining the effects of psychological treatments, with a total of 1628 subjects. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
171
2
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(209 citation statements)
references
References 59 publications
15
171
2
10
Order By: Relevance
“…Literature has shown that the intervention for social anxiety is mainly focused on psychological approaches (Acarturk et al, 2009;Heimberg & Barlow, 1988;Yang et al, 2013). Previous studies proposed effective intervention techniques based on various theories, of which cognitive behavior modification (CBM) had been demonstrated the strongest evidence (Evans et al, 2008;Salovey & Singer, 1991;Chang & Chien, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Literature has shown that the intervention for social anxiety is mainly focused on psychological approaches (Acarturk et al, 2009;Heimberg & Barlow, 1988;Yang et al, 2013). Previous studies proposed effective intervention techniques based on various theories, of which cognitive behavior modification (CBM) had been demonstrated the strongest evidence (Evans et al, 2008;Salovey & Singer, 1991;Chang & Chien, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 70% of cases are categorized as severe or moderate. 2 Cognitive behavioral therapy (CBT) has been shown to be effective in SAD, 3 but 40 to 50% of patients show little or no improvement after treatment. 4 Although CBT has recently been refined to target more specific cognitive processes believed to maintain and exacerbate symptomatology, 5,6 leading to greater reductions in selfreported social anxiety symptoms than earlier protocols, newer cognitive behavioral strategies are still needed to maximize treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Tais achados são confi rmados por Acarturk et al 52 em estudo meta-analítico recente que afi rmou também que essa efi cácia tende a se manter e, em alguns casos, até melhorar nas medidas de follow-up. Contudo, na análise entre os subgrupos que incluíam RC, EXP, THS e relaxamento aplicado, não foram encontrados altos effect sizes, pois a maioria dos ensaios avaliados misturava essas técnicas e outros poucos as examinaram isoladamente.…”
Section: Discussionunclassified